Kajian Budaya Organisasi Bina Nusantara University Menuju “A World Class University” - Amia Luthfia; Agus Wasita; Rosidah Syaukat (Humaniora, 2013)
University is an important institution that would form the nation culture and responsible for the culture transmission. The assessment of a good organizational culture is an important part in the study of organizational culture. The research objective is to analyze organizational culture of Bina Nusantara University comprehensively, the strengths and weaknesses of its effort to become “The World Class University". The research methodology is qualitative with method combination of FGD, in-depth interviews and covert observation. The research outcome shows that Bina Nusantara University has had elements of modern organization characteristic such as innovative management (centralized non-academic function and decentralize academic function); transparent and results-oriented management system with clear and measurable target; detail operational procedure. It has been able to create healthy working environment that supports high integrity, working ethics, dedication, loyalty, opened communication and high sense of belonging. It utilizes information and communications technology through a comprehensive and integrated system called Binusmaya as its ikon and identity.As an educational institution, Bina Nusantara University should develop 3 other elements which are role model, spirit and character building. Former rector (the founder) was an inspired role model that provided a profound influence to the attitudes and behaviors of its members.